Prevalence of Campylobacter among goats and retail goat meat in Congo - Rosette Kabwang a Mpalang; Raphaël Boreux; Pierrette Melin; Khang'Mate Akir Ni Bitiang; Georges Daube; Patrick De Mol (Journal of Infection in Developing Countries)
Background: The prevalence of Campylobacter jejuni and Campylobacter coli was determined in goat and goat meat sold at retail outlets in Lubumbashi, Democratic Republic of Congo (DR Congo). Methodology: A total of 644 samples, including 177 goat meat, 86 goat stomachs, 139 ready to eat (RTE) goat skewers, and 242 goat faecal samples were examined for the presence of Campylobacter jejuni and Campylobacter coli using polymerase chain reaction. Results: Overall, Campylobacter spp. were found in 34.6% of the examined samples. C. jejuni was isolated in 10.1% and C. coli in 26.7% of samples. Only 2.2% of all samples were positive for both species. There was a significant association between the prevalence of C. coli and the type of sample (p < 0.05). The overall prevalence of Campylobacter in different sample groups was 41.2%, 37.2%, 23.7%, and 35.1% for goat meat, goat stomachs, RTE goat skewers, and goat faecal samples, respectively. There was no significant difference (p > 0.05) between the prevalence observed in the rainy season (16.7%) and the dry season (20.0%). Moreover, the overall prevalence of Campylobacter in slaughter sites, open-air markets, warehouses, and semi-open-air markets was 28.2%, 34.2%, 35.4%, and 42.9%, respectively. Statistically, there was no influence of the sample collection site on the frequency of isolation of Campylobacter (p > 0.05). Conclusion: This study shows that, considering the relatively high prevalence of this pathogen, live goat and goat meat are major sources of human and environmental contamination by Campylobacter spp. in Lubumbashi.